If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p(x) = 5 + -10x Multiply p * x px = 5 + -10x Solving px = 5 + -10x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by 'x'. p = 5x-1 + -10 Simplifying p = 5x-1 + -10 Reorder the terms: p = -10 + 5x-1
| (2/x-2)=(x/x^2-8) | | 3(8-x)=6x+15 | | 0=35+9.8x | | 0.18y+0.07(y+4000)=280 | | -300+3Q=Q^2 | | cx+hy=jx | | xc+hy=j | | 1052=X*(3.6/5)*70 | | 8k+7=6k+19 | | 2(x-5)+1=3(x-1)+5 | | 1052=X*(3.6/5)*Y | | 4(5x-3)=x+7 | | 2(x-1)=2(-1+x) | | -7(9x-5)=-8 | | 2=2(x-3)+1-x | | Y7/y5 | | 2x^2-7x+3ifx=-2 | | -9(v+4)+4v+6=5v+11 | | -8u+2(u-6)=-24 | | X=a+y+5 | | X=a-y-5 | | X^2-2x+3.25=0 | | (2)-(3)+2(1)+3(-2)= | | x^4-10x^2-x+18=0 | | ln8-3ln1/2 | | ln8-3ln(1/2) | | 3/4=7/a | | 3/2=7:a | | (x-2)(x+8)=2 | | 9y+3-2y+7= | | 6(X+5)-(4x-4)= | | 2(3p-1)-3(p-4)= |